Hubungan Kecenderungan Neurotik dengan Subjective Well-Being pada Mahasiswa yang Menyelesaikan Skripsi - Ria Wiyatfi (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2022)
The process of completing the thesis of bachelor faced by students often causes stress that affects their welfare which is called subjective well-being. One of the factors that influence the subjective well-being of individuals is the personality tendency factor. This study discusses the relationship between neurotic tendencies and subjective well-being. Participants in this study were students of the Faculty of Psychology, University of X who were working on a thesis. The type of research used in this research is correlational quantitative research between two variables using a neurotic tendency scale and a subjective well-being scale. The results of this study indicate that there is a relationship between neurotic tendencies and subjective well-being. The relationship between neurotic tendencies and subjective well-being showed a significant negative correlation (r = -0.221, p = 0.016). The lower the neurotic tendency, the higher the subjective well-being. The higher aspect of being owned by students in subjective well-being is affective evaluation, which is 41.5%.